Effect of the presence of fluid on the dynamic response of buried orthotropic cylindrical shells under a moving load - Kota V.N.; Singh V.P. (My University, 2025)
This paper deals with the theoretical analysis of the axisymmetric steady state dynamic response of a buried fluid-filled orthotropic cylindrical shell subjected to a radial line load moving along the axis of the shell. A thin shell is assumed to be perfectly bonded to the surrounding medium of infinite extent, and only the axisymmetric response has been included. A linear acoustic equation has been used for the wave propagation in fluid. The nature of variation of differences between the results of the empty and fluid-filled shells has been studied for varying soil conditions. Changes in results due to variation in the orthotropy parameters have been compared with the difference in results due to the presence of fluid inside the shell. © 1991.